2013
DOI: 10.4161/auto.22831
|View full text |Cite
|
Sign up to set email alerts
|

IFNB1/interferon-β-induced autophagy in MCF-7 breast cancer cells counteracts its proapoptotic function

Abstract: IFNB1/interferon (IFN)-β belongs to the type I IFNs and exerts potent antiproliferative, proapoptotic, antiangiogenic and immunemodulatory functions. Despite the beneficial effects of IFNB1 in experimental breast cancers, clinical translation has been disappointing, possibly due to induction of survival pathways leading to treatment resistance. Defects in autophagy, a conserved cellular degradation pathway, are implicated in numerous cancer diseases. Autophagy is induced in response to cancer therapies and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 84 publications
7
54
0
1
Order By: Relevance
“…In contrast, we have recently reported that endoplasmic reticulum stress in hyperoxia-and IFNg-induced mouse models of BPD was associated with increased apoptotic cell death, although no data on autophagy were reported (39). In breast cancer lines, IFN-b induced autophagy upstream of MTORC1, whereas the proapoptotic function was significantly increased in the absence of autophagy (40). In such a scenario, inhibition of autophagy would be considered clinically more important.…”
Section: Original Researchmentioning
confidence: 65%
“…In contrast, we have recently reported that endoplasmic reticulum stress in hyperoxia-and IFNg-induced mouse models of BPD was associated with increased apoptotic cell death, although no data on autophagy were reported (39). In breast cancer lines, IFN-b induced autophagy upstream of MTORC1, whereas the proapoptotic function was significantly increased in the absence of autophagy (40). In such a scenario, inhibition of autophagy would be considered clinically more important.…”
Section: Original Researchmentioning
confidence: 65%
“…In addition, there is also evidence for IFN-dependent induction of autophagy (Ambjørn et al, 2013; Schmeisser et al, 2014). We determined whether inhibition of autophagy modulates IFN-dependent transcriptional activation.…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunction of the autophagic pathway has been implicated in various diseases, including cancer, obesity, cardiac disease, neurodegeneration, aging, infection and inflammatory diseases (17)(18)(19). However, the role of autophagy in association with cancer and tumorigenesis is complex and highly context-dependent (20). Autophagy may be involved in cell cycle regulation, apoptosis, angiogenesis and other aspects of tumor initiation and progression (21).…”
Section: Discussionmentioning
confidence: 99%